Pathophysiology, Prevalence, and Management of Iron Deficiency Anemia - Ugle, Deepali; Bhanage, Avani; S. Ugle, S.; Shinde, Ekta (International Journal of Nursing Research, 2023)
Anemia is a major killer in India. Statistics reveal that every second Indian woman is anemic. One in every five maternal deaths is directly due to anemia. Anemia affects both adults and children of both sexes, although pregnant women and adolescent girls are most susceptible and most affected by this disease. Iron deficiency is the most common micronutrient deficiency which affects more than 2 billion population worldwide, leading to anemia in more than 40% of women of reproductive age developed countries. The prevalence of anemia among adolescent is more than 25% in developing countries. Globally, anemia affects 1.6 billion people which correspond to 24.8% of the population. The highest prevalence is in the preschool age children 47.4%, prevalence in men is 12.7% the groups with higher prevalence are, infants and children of 1–2 years 48%, School children are about 40%, non-pregnant women 35%, adolescents 30–55%, and preschool children 25%. The prevalence of anemia in developing countries is about 4 times than those of developed countries. Asia has the highest rates of anemia in the world. About half of the world’s anemic women live in Indian subcontinent and 88% of them develop anemia during pregnancy. The situation in Asia has not improved in recent years. Almost all individuals will be iron deficient except possibly if the anemia is caused predominantly by malaria. This review contains detailed information about types and prevalence of anemia, including special emphasis of pathophysiological aspects and treatment management of iron deficiency anemia.